Self-transcendence through Futuwwah and Dharma: Islam and Hinduism Perspectives - Sefa Bulut (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2021)
As a field of study, psychology has been on the path of sustained evolution. From psychoanalysis to Logotherapy, we have come a long way. The advent of spirituality, positive thinking, and the renewed interest in human potential have led to the emergence of various sub-fields in psychology. From denying the role of religion and spirituality in the therapy setting to designing interventions around these concepts, we have approached a contemporary phase in understanding human behavior and attitudes. A novel concept born out of the evolution of psychological concepts is the idea of self-transcendence. According to Maslow, there is a progressive movement towards uncovering people’s potentials and being the best version of the self. Maslow proposed that a self-actualizing individual would eventually have to move up the hierarchy of needs and transcend the ego to relate to something beyond it. This process, known as self-transcendence, is often facilitated by selfless values and moral behaviors that allow the ego to transcend itself. The present paper looks into Maslow’s theory of self-transcendence as recorded in two particular religious philosophies; Futuwwah (Islam) and Dharma (Hinduism). Both Futuwwah and Dharma, despite cultural and religious differences, foster similar values and moral acts in people. The current paper attempts to establish that the moral acts prescribed in Futuwwah and Dharma would eventually lead to an individual's self-transcendence. To do so, we will first attempt to define self-transcendence, theories of self-transcendence from multiple disciplines, and related concepts such as peak experiences and flow. Further, the paper will strive to explore traces of self-transcendence as expressed in religious philosophies, namely; Futuwwah and Dharma.